Writing Assessment Literacy: Investigating EFL Teachers' Writing Assessment Practices in A Vocational School - Munasih, Dian Septia; Prastikawati, Entika Fani; Wiyaka, Wiyaka; Adeoye , Moses Adeleke (Universitas PGRI Semarang, 2024)
The study examines English Teachers’ knowledge and attitudes concerning different assessment methods in SMK Ky Ageng Giri. Understanding assessment concepts helps teachers choose and create the best methods to assess students. How much SMK instructors Ky Ageng Giri knew about writing assessment and if they had formal training before instructing are two major research topics. Three SMK Ky Ageng Giri English teachers complete open-ended surveys and classroom observations. The poll found that most individuals had some formal training, but 33.3% had none. All teachers claimed they had no formal assessment writing training. More than half complained about creating evaluation projects to evaluate their students. The open-ended questionnaire answers match class practice and evaluation background. The study aims to evaluate the implementation of current educational programs in classrooms and identify assessment writing concerns among English teachers to inspire Vocational School teachers to review their assessment processes.